Persepsi Mahasiswa tentang Makna Barokah dalam Khataman aL-Quran di Universitas Islam Negeri Salatiga - Emawati, Emawati (Institute of Research and Public Service Universitas Jenderal Soedirman, 2024)
The study investigated the perceptions of students on the tradition khataman al-Quran at Islamic college. This research was conducted with intensive field work in UIN Salatiga, Central Java. A visit to the area opened an opportunity to make involved observations, which helped to understand the daily social life among students in Salatiga. In selecting informants, purposive sampling techniques were used and interviewed s even key informants and sixty secondary informants used to distribute a google form with a list of questions. The results revealed that the perception of blessings in the Khataman al-Quran is interpreted differently by students, depending on gender and domicile. The majority of students who live in Islamic boarding schools understand the meaning of blessingas referring to the general meaning: Blessings are goodness, people who receive blessings from Allah are marked by increasing the quality of good deeds in their lives. Meanwhile, students who live outside the Islamic boarding school understand that the substance of the khataman tradition is to gain rewards and ease in living life.